The right to disconnect - Valencia-Tello, Diana (Revista Chilena de Derecho y Tecnología, 2024)
Each industrial revolution has a particular way of organizing work and production in industries, which impacts the structure of jobs and with it the rights and obligations of workers. Currently, the fourth industrial revolution and the covid 19 have strengthened the digitization of many production processes and with it have modified the traditional structure of jobs. In this context, work disconnection is a new type of right, where due to the difficulties of regulating the working day under the same parameter, countries are appealing to self-regulation of organizations through collective agreements or internal regulations, in order to establish disconnection policies and thereby guarantee the rest that every worker requires to stay productive. This new regulatory dynamic requires State control and surveillance to be effective and its impact is essential to promote decent work and economic growth in accordance with objective 8 of the 2030 Agenda for Sustainable Development.